Ca2+-dependent desensitization of insulin secretion by strong potassium depolarization - Willenborg, Michael; Schumacher, Karin (American journal of physiology. Endocrinology and metabolism, 2012)
Depolarization by a high K+ concentration is a widely used experimental tool to stimulate insulin secretion. The effects occurring after the initial rise in secretion were investigated here. After the initial peak a fast decline occurred, which was followed by a slowly progressive decrease in secretion when a strong K+ depolarization was used. At 40 mM KCl, but not at lower concentrations, the decrease continued when the glucose concentration was raised from 5 to 10 mM, suggesting an inhibitory effect of the K+ depolarization. When tolbutamide was added instead of the glucose concentration being raised, a complete inhibition down to prestimulatory values was observed. Equimolar reduction of the NaCl concentration to preserve isoosmolarity enabled an increase in secretion in response to glucose. Unexpectedly, the same was true when the Na+-reduced media were made hyperosmolar by choline chloride or mannitol. The insulinotropic effect of tolbutamide was not rescued by the compensatory reduction of NaCl, suggesting a requirement for activated energy metabolism. These inhibitory effects could not be explained by a lack of depolarizing strength or by a diminished free cytosolic Ca2+ concentration ([Ca2+]i). Rather, the complexation of extracellular Ca2+ concomitant with the K+ depolarization markedly diminished [Ca2+]i and attenuated the inhibitory action of 40 mM KCl. This suggests that a strong but not a moderate depolarization by K+ induces a [Ca2+]i-dependent, slowly progressive desensitization of the secretory machinery. In contrast, the decline immediately following the initial peak of secretion may result from the inactivation of voltage-dependent Ca2+ channels.